Potential hepatoprotective effects of Cistanche deserticola Y.C. Ma: Integrated phytochemical analysis using UPLC-Q-TOF-MS/MS, target network analysis, and experimental assessment - Wang, Haichao; Li, Yaying; Bian, Yifei; Li, Xue; Wang, Yubei; Wu, Ke; Liu, Chuanguo; Liu, Yuhong; Wang, Xiaoming (Frontiers in Pharmacology, 2022)
Cistanche deserticola Y.C. Ma (CD) possesses hepatoprotective activity, while the active ingredients and involved mechanisms have not been fully explored. The objective of this study was to investigate the chemical composition and hepatoprotective mechanisms of CD. We primarily used ultra-performance liquid chromatography with quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF-MS/MS) to identify the phenylethanoid glycoside (PhG) components of CD. Then, network analysis was used to correlate and predict the pharmacology of the identified active components of PhGs with hepatoprotection. Next, the mechanisms of the core components and targets of action were explored by cellular assays and toll-like receptor 4 (TLR4) target competition assays. Finally, its hepatoprotective effects were further validated in in vivo experiments. The results showed that a total of 34 PhGs were identified based on the UPLC-Q-TOF-MS/MS method. Echinacoside (ECH) was identified as the key ingredient, and TLR4 and nuclear factor-kappa B (NF-κB) were speculated as the core targets of the hepatoprotective effect of CD via network analysis. The cellular assays confirmed that PhGs had significant anti-inflammatory activity. In addition, the real-time quantitative polymerase chain reaction (RT-qPCR) and Western blot indicated that ECH notably reduced the levels of interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α), as well as the mRNA expression of TLR4, TNF-α, and IL-6, and decreased the high expression of the TLR4 protein, which in turn downregulated the myeloid differentiation factor 88 (MyD88), p-P65 and TNF-α proteins in the inflammatory model. The target competition experiments suggested that ECH and LPS could competitively bind to the TLR4 receptor, thereby reducing the expression of TLR4 downstream proteins. The results of in vivo studies showed that ECH significantly ameliorated LPS-induced hepatic inflammatory infiltration and liver tissue damage and reduced serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in mice. Moreover, ECH remarkably inhibited the release of inflammatory factors such as TNF-α, IL-6, IL-1β, and MCP-1 in the serum of mice, exerting the hepatoprotective effect by the TLR4/NF-κB signaling pathway. More importantly, ECH could act as a potential inhibitor of TLR4 and deserves further in-depth study. Our results could provide a basis for exploring the hepatoprotective properties of CD.